EFFECTS OF COVID19 ON FOOD SECURITY IN WESTERN AGRICULTURAL ZONE OF BAUCHI STATE, NIGERIA - Bello, I. S.; Abdullahi, S.; Bala, A. H. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study examined the effects of Covid-19 on food security in Western Zone of Bauchi State, Nigeria. Multi-stage sampling technic was employed in selecting 200 respondents for the study. Data were obtained using structured questionnaires and analyzed using both descriptive and inferential statistics. The result reveals that majority (79.5%, 77.5% and 73%) of the respondents were primarily farmers, non-members of cooperatives and agree that covid19 affects household food security, respectively. The findings also shows that majority (75%, 69% and 60.5%) of the respondents were male, married and had no access to extension contact. The mean age and household size of the respondents were 42 years and 8 person respectively. The result also show that the mean farm size, income and years’ experience of the respondents were 2.1ha, ₦319,725 and 7 years, respectively. The findings also reveals that socioeconomic factors such as marital status, educational level and occupation were significant (P<0.01 and P<0.05) in influencing food insecurity among farming households. The results further reveals that fear of disease contraction, high cost of transportation and bias in palliative distribution were the major constraints to food security and were ranked 1st, 2nd and 3rd, respectively. The study concludes that marital status, educational level and occupation were the factors influencing food insecurity. Based on the findings the study recommends that farming household should obey medical instructions to avoid disease contraction, farmers should form cooperative in order to ease cost of transportations and government should involve farmers’ cooperatives in palliatives distribution.